PENGARUH ZIKIR AL-MA’TSURAT DAN TERJEMAHANNYA TERHADAP PENURUNAN KECEMASAN SISWA MENGHADAPI UJIAN NASIONAL - Jannah, Nur (Jurnal Studia Insania, 2017)
The problems most often experienced by students when facing the National Exam is anxiety problems. Anxiety arises because students are burdened by thoughts and shadows of possibilities that occur when failing in the National Exam. Excessive anxiety will cause students not to focus on the National Exam. One way that can be done to provide peace of mind in the Islamic view is with dhikr. In contrast to most schools, SMPIT Ukhuwah Banjarmasin not only prepares students in the outer field such as additional subjects are tested, but the school also prepares the spiritual condition of students by giving the program of recitation of al-Ma?tsurat recitation that is read every afternoon. But the recitation of the dhikr is not with the translation. The reading of al-Ma?tsurat dhikr with its translation will invite the students to be more solemn and understand the content contained in the recitation of the dhikr. This study aims to determine the level of student anxiety and find out whether the dhikr al-Ma?tsurat and its translation have an effect on the decreasing anxiety of students facing the National Exam at SMPIT Ukhuwah Banjarmasin.This research is experimental research and data is presented with quantitative approach. Variable in this research there are 2 that dhikr al-Ma?tsurat and translation (X) and anxiety (Y). While the design of this study using the design pretest and posttest one group. Data collection tools in the form of anxiety scale The sampling technique used is purposive sampling, with the number of subjects as many as 7 students. Data analysis using t-test.The results of quantitative data indicate a decrease in anxiety between before the intervention (pretest) and after intervention (postest) is done, the scoring of the anxiety category from high to medium and low anxiety categories. And the decline of a large minimum value of 32.00 and the maximum value of 24.00, and the mean value of 24.7147. The result of the normality prerequisite test is p> 0,05 indicating that the data distribution at initial and final test is normal. The result of t-test is obtained t value = 11,068 and p = 0,000, p <0,01, meaning dhikr al-Ma?tsurat  and its translation can influence decreasing anxiety of student facing National Exam at SMPIT Ukhuwah Banjarmasin.